Fuzzy models of algorithms reliability, taking into account various types of errors - Rotshtein, O. P.; Shtovba, S. D.; Kozachko, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers fuzzy models of algorithmic structures reliability for multidimensional concept of errors accounting. The novel of the suggested work is that unlike fuzzy theory of reliability, these models allow to take into consideration various types of errors of algorithm performance, and unlike matrix models of algorithmis structures of reliability they provide the account of fuzzy initial information regarding the reliability of operands and logic conditions.